Cranially-based nasolabial flaps for the reconstruction of nasal surgical defects - Kerem, Hakan (Arch Plast Surg, 2018)
BACKGROUND: Cranially-based nasolabial flaps are a good alternative for the reconstruction of nasal defects. METHODS: A cranially-based nasolabial flap was used in 18 patients to reconstruct defects of the nose from 2010 to 2016, and the long-term results are presented in this report. RESULTS: Fifteen of the flaps completely survived. All the patients had a bulky appearance, but they did not want to undergo a second operation for cosmesis. The dissection of the flap took approximately 20 minutes, and the total operation lasted for 1 hour. The patients were hospitalized for 1–7 days, and the postoperative follow-up period was 1–28 months (mean, 17 months). CONCLUSIONS: The cranially-based nasolabial flap possesses all the advantages of the traditional forehead flap, and can safely be used in selected cases.